2005
DOI: 10.1111/j.1467-8624.2005.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily Reports of Witnessing and Experiencing Peer Harassment in Middle School

Abstract: Two studies examined daily incidents of peer harassment in urban middle schools. Sixth-grade students (M age = 11 years) described their daily personal experiences and witnessed accounts of peer harassment, and rated their negative feelings across a 2-week period. In Study 1 (n = 95), within-subject analyses across 4 days revealed that both personally experienced and witnessed harassment were associated with increases in daily anxiety, whereas witnessing harassment buffered students against increases in humili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
200
5
12

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(237 citation statements)
references
References 56 publications
13
200
5
12
Order By: Relevance
“…In their study, social disorder was operationalized as the classroom level of aggression and victimization. Nishina and Juvonen (2005) found that observed victimization buffered against the negative effects of experienced victimization: the negative effects were mitigated for those victimized students who also saw others being harassed in their environment. Huitsing et al (2012) found that victimization was related to maladjustment especially in classrooms where 1) the average level of victimization was low or 2) victimization was highly centralized, in other words targeted at few specific students rather than Ba little bit on everyone^.…”
Section: The 'Healthy Context Paradox'mentioning
confidence: 95%
“…In their study, social disorder was operationalized as the classroom level of aggression and victimization. Nishina and Juvonen (2005) found that observed victimization buffered against the negative effects of experienced victimization: the negative effects were mitigated for those victimized students who also saw others being harassed in their environment. Huitsing et al (2012) found that victimization was related to maladjustment especially in classrooms where 1) the average level of victimization was low or 2) victimization was highly centralized, in other words targeted at few specific students rather than Ba little bit on everyone^.…”
Section: The 'Healthy Context Paradox'mentioning
confidence: 95%
“…However, many children experience several of these different victimizations (Saunders, 2003). For one thing, the sheer frequency of victimizations in childhood suggests that some of these victimizations should overlap (Nishina & Juvonen, 2005). In addition, most victimizations seem to have common correlates, like family instability or neighborhood disorder.…”
mentioning
confidence: 99%
“…Children have a much harder time resisting this self-blame when they experience victimization from multiple sources. Another possibility is that because victimization is so common, children do not see themselves as stigmatized on this dimension, unless they are experiencing multiple sorts of victimization (Nishina & Juvonen, 2005).…”
mentioning
confidence: 99%
“…The participants usually write 3 to 4 lines about their experiences Nishina and Bellmore (2010). However, some researchers have tried more longitudinal studies that span several months to years Nishina and Juvonen (2005); Nylund et al (2007). Despite surveys being the most widely adopted method, there are several limitations of this method.…”
Section: Bullying Detection On the Webmentioning
confidence: 99%